Terpenoids and membrane dynamics evolution - Hoshino, Yosuke (Frontiers in Ecology and Evolution, 2024)
Cellular membranes define the physical boundary of life and provide scaffolds for various fundamental metabolic activities, including ATP synthesis, respiration, phototrophy, endocytosis and ion transport. Terpenoids, also known as isoprenoids, are known to play important roles in membrane organization and regulation across the three domains of life through unique interactions with other membrane lipids and membrane proteins. Terpenoids are present in not only the membranes of the three domains, but also viral membranes and extracellular vesicles. The large structural diversity of terpenoids and their ubiquitous distribution in modern organisms make terpenoids distinct from other membrane lipids, such as fatty acyls that are nearly absent in archaea.Addressing the biochemical and biophysical properties that allow terpenoids to play critical roles in membrane organization is important to understand the driving forces that shaped cellular life as we know it. This review summarizes the major classes of terpenoids that are involved in membrane organization and discuss the impact of terpenoid-membrane interactions on the evolutionary trajectory of membrane dynamics and the fitness of host organisms.